1992
DOI: 10.1111/j.1751-1097.1992.tb04225.x
|View full text |Cite
|
Sign up to set email alerts
|

STRAND BREAKAGE IN POLY(C), POLY(A), SINGLE‐AND DOUBLE‐STRANDED DNA INDUCED BY NANOSECOND LASER EXCITATION AT 193 nm*

Abstract: Single- and double-stranded calf thymus DNA and two polynucleotides (0.4 mM) were studied in aqueous solution at pH approximately 7 using pulsed, 20 ns laser excitation at 193 nm. Monophotonic ionization of the nucleic acids is suggested from the linear dependences of the concentration of ejected electrons and the number of single- and double-strand breaks (ssb, dsb, respectively) on laser intensity (IL) in the range (0.2-3) x 10(6) W cm-2. The quantum yields of formation of hydrated electrons (phi e-) and ssb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In poly(C), the kinetics of SO 4 ؒϪ -induced strand breakage shows a ∼15% slow contribution that is very similar to that of the ؒ OH-induced reaction. 31 In the present context, the most important observation is that strand breakage induced by photoionisation 32 which has to proceed via a free radical cation is not suppressed by dioxygen in contrast to the SO 4 ؒϪ -induced reaction. 31 This is very strong evidence that a free cytosine radical cation is not involved to a major extent in the SO 4 ؒϪinduced reaction and that the reaction proceeds mainly by a nucleophilic attack by the C(2Ј)OH as depicted in reaction (9).…”
Section: Relevance Of the Present Results To Somentioning
confidence: 89%
See 1 more Smart Citation
“…In poly(C), the kinetics of SO 4 ؒϪ -induced strand breakage shows a ∼15% slow contribution that is very similar to that of the ؒ OH-induced reaction. 31 In the present context, the most important observation is that strand breakage induced by photoionisation 32 which has to proceed via a free radical cation is not suppressed by dioxygen in contrast to the SO 4 ؒϪ -induced reaction. 31 This is very strong evidence that a free cytosine radical cation is not involved to a major extent in the SO 4 ؒϪinduced reaction and that the reaction proceeds mainly by a nucleophilic attack by the C(2Ј)OH as depicted in reaction (9).…”
Section: Relevance Of the Present Results To Somentioning
confidence: 89%
“…These results will also be relevant for the understanding of the marked mechanistic differences of strand break formation in poly(C) induced by SO 4 ؒϪ radicals 31 and by photoionisation. 32 The now available information will allow us to support but also to modify in some essential aspects the present view 23,27 on the two so differently behaving systems, 1a and 1b.…”
Section: ϫmentioning
confidence: 86%
“…In our study, a very slight difference in the yield of prompt strand breakage was found for samples irradiated under aerated conditions, as compared with argon-saturated conditions ( Table 1). Gomer et al (2) found that the quantum yield of ssb induced by photolysis with 193 nm light for calf thymus DNA is 4.5 X in aerated solutions. Gurzadyan and Gomer (34) reported the quantum yield of base release from double-stranded calf thymus DNA and this is (€"baserelease (193 nm…”
Section: Discussionmentioning
confidence: 99%
“…The advent of shortwave UV lasers has enabled the study of the direct ionization processes to be studied without the interaction of the ionization products of water (1). Photoionization of aqueous solutions of DNA with 193 nm laser light results in the formation of a photoejected electron via a monophotonic process (2). The DNA radicals formed by photoionization are proposed precursors of low yields of single strand breaks (ssb)t (1,3,4), which we have recently confirmed using Rayleigh light scattering experiments (5).…”
Section: Introductionmentioning
confidence: 99%
“…7 This review is devoted to the analysis of the most important photosensitised, oxygen-independent free-radical and electrophilic addition reactions. One-photon 17,18 and two-photon 19,20 photochemical reactions of NA induced by far UV light (190 ± 300 nm), photooxidation of DNA with singlet oxygen 3,7,21 and radical species 22 ± 24 as well as oxidation caused by photoinduced electron transfer 11,25,26 have been studied in sufficiently great detail and will not be considered in this review.…”
Section: Introductionmentioning
confidence: 99%